1976
DOI: 10.1055/s-0028-1104201
|View full text |Cite
|
Sign up to set email alerts
|

Isoenzyme der Kreatinkinase bei extrakardialen Erkrankungen und nach diagnostischen und therapeutischen Eingriffen

Abstract: Creatine kinase MB isoenzyme was measured (using antibody inhibition) in serum of patients with exogenous intoxication, acute pancreatitis, cerebrovascular accidents, meningitis, encephalitis, skeletal muscle disease, shock, postoperative states and after coronary arteriography, cardiac catherisation of cardioversion. CK-MB activity was revealed only in sera of patients with exogenous intoxication (severity III and IV), polymyositis, scleroderma, after operation or after coronary arteriography, cardiac catheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
7

Year Published

1978
1978
1987
1987

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 0 publications
0
6
0
7
Order By: Relevance
“…This is probably due to the fact that in the majority of the conditions studied (i.e. head injuries, cerebrovascular disease, tumours, meningitis), central nervous system (CNS) involvement is widespread and/or massive, and thus no conclusion about the pathogene sis of these conditions can be reached [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…This is probably due to the fact that in the majority of the conditions studied (i.e. head injuries, cerebrovascular disease, tumours, meningitis), central nervous system (CNS) involvement is widespread and/or massive, and thus no conclusion about the pathogene sis of these conditions can be reached [1][2][3][4][5][6][7][8].…”
mentioning
confidence: 99%
“…In the study reported here, we made the first attempt to detect possible myocardial damage resulting from fairly long-term treatment with a /3-adrenergic drug using an objective biochemical parameter, that is to say measuring creatine kinase MB activity. This creatine kinase isoenzyme is of proven sensitivity (7,9,10,15). The results show that there is evidently no necrosis-type myocardial damage even with long-term tocolytic treatment with the relatively high dosage of 0.24 mg fenoterol/h.…”
Section: Discussionmentioning
confidence: 99%
“…This is done by measuring the activity of the isoenzyme of creatine kinase, creatine kinase MB, which, to a large extent, is specific to heart muscle (7,12,15). This technique is just as reliable as the ECG for indicating myocardial necrosis (9,10,15).…”
mentioning
confidence: 99%
“…Höhere Aktivitäten entsprechen einer pathologischen Kreatinkinase-MB-Aktivität. Dieser Grenzwert stimmt mit den für die Kreatinkinase-MB (GSH-aktiviert) mitgeteilten Befunden (10,13), die inzwischen vielfach über-prüft wurden (9,17,(21)(22)(23)(24)(25) …”
Section: Kreatinkinase-mb -Entscheidungsgrenzeunclassified
“…und Alanin-aminotransferase, -Glutamyltransferase undHydroxybutyratdehydrogenase sowie der Kreatinkinase (GSHaktiviert, (3)) und ihres Isoenzyms MB (GSH-aktiviert, (10)). Bei 66 Patienten mit klinisch und elektrokardiographisch gesichertem, aktutem, trahsmuralem Myokardinfarkt (14) wurde die Aktivität der Kreatinkinase (359 Messungen, jeweils GSHund N-Acetylcystein-aktiviert) und der Kreatinkinase-MB (293 Messungen, jeweils GSH-und N-Acetylcystein-aktiviert) gemessen.…”
unclassified